2023
DOI: 10.26434/chemrxiv-2023-p40nn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Weyl Semimetals MIrTe4 (M = Nb, Ta) as Efficient Catalysts for Dye-sensitized Hydrogen Evolution

Abstract: The prevalent global energy crisis calls for searching viable pathways for generating green hydrogen as an alternative energy resource. Dye-sensitized photocatalytic water splitting is a feasible solution to produce green hydrogen. However, identifying suitable catalysts has been one of the bottlenecks in driving dye-sensitized photocatalysis efficiently. In this work, we report a new class of electrocatalysts based on the layered Weyl semimetals MIrTe4 (M = Nb, Ta) for the Eosin Y (EY)-sensitized hydrogen evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Remarkably, the two above-mentioned properties have been experimentally confirmed. 11,[26][27][28] In fact, recent research results have also confirmed the feasibility of topological materials, such as topological insulators Bi 2 Se 3 and Bi 2 Te 3 , 29,30 Weyl semimetal TaAs family, 8 TaTe 4 31 and NiSi, 32 multifold degenerate semimetals PtGa, PtAl, Nb 2 S 2 C and C12A7:4e À , [33][34][35] nodal line semimetal TiSi family 22 and semiconductor MoS 2 with floating surface states 36 in the field of catalysis. At present, the topological quantum catalysts are still in the initial stage, and exploring ideal topological quantum catalysts is particularly important.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Remarkably, the two above-mentioned properties have been experimentally confirmed. 11,[26][27][28] In fact, recent research results have also confirmed the feasibility of topological materials, such as topological insulators Bi 2 Se 3 and Bi 2 Te 3 , 29,30 Weyl semimetal TaAs family, 8 TaTe 4 31 and NiSi, 32 multifold degenerate semimetals PtGa, PtAl, Nb 2 S 2 C and C12A7:4e À , [33][34][35] nodal line semimetal TiSi family 22 and semiconductor MoS 2 with floating surface states 36 in the field of catalysis. At present, the topological quantum catalysts are still in the initial stage, and exploring ideal topological quantum catalysts is particularly important.…”
Section: Introductionmentioning
confidence: 80%
“…At present, the study and calculations of topological catalysts using PBE-D2 have obtained good test results. [29][30][31][32][33][34][35][36] The HER of Mg 3 Bi 2 was performed in the supercell structure of dimension 2 Â 2 Â 4.…”
Section: Calculation Methodsmentioning
confidence: 99%